ATHEROMATOSIS OF ARTERIAL INTIMA AS A RESULT OF THE BIOLOGICAL FUNCTION OF ENDOECOLOGY, BIOLOGICAL REACTION OF INFLAMMATION AND UTILIZATION OF NON-LIGAND PALMITIC VERY LOW DENSITY-LOW DENSITY LIPOPROTEINS - V. N. Titov; B. B. Shoybonov (Евразийский Кардиологический Журнал, 2016)
Phylogenetically late intima of elastic arteries has no proteins for transportation of non-ligand oxidized low density lipoproteins (LDL) adsorbed on the matrix to resident macrophages. Phylogenetically early cells realize the reaction of extracellular digestion by secreting the proteolytic enzymes metalloproteases in the matrix. They hydrolyze matrix proteoglycans, adsorbed and non-ligand LDL, absorb detritis, and terminate hydrolysis of the most hydrophobic polyenic cholesterol esters (poly-CE) in lysosomes. Smooth muscle cells migrate from arterial media, change their phenotype from contractile to synthetic and produce in situ de novo matrix proteoglycans. Elastic arterial wall consists of three layers: a) endothelial monolayer, b) intima + media (smooth muscle cells) and b) adventitia. It seems reasonable to define functional differences between phylogenetically early resident macrophages and phylogenetically late monocytes-macrophages. They may be associated with scavenger receptors, CD36 translocase activity, production of acid hydrolases for poly-CE or realization of the biological reaction of extracellular digestion. We suppose that atheromatous masses are formed in the matrix of arterial intima but not in lysosomes when the ability of monocytes-macrophages to provide endocytosis of non-ligand LDL from the matrix is limited. If atheromatosis is a syndrome caused by intracellular deficiency of essential polyenic fatty acids (PFA), intimal atheromatosis is associated with partial utilization of excess PFA in the matrix of elastic arteria. At late stages of phylogenesis the intima formed from smooth muscle cells of the media.